Organ donation from burn-injured patients—a national perspective - Travis, Taryn E.; Johnson, Laura S.; Moffatt, Lauren T.; Subramanian, Ram M.; Jordan, Marion H.; Shupp, Jeffrey W. (The Journal of surgical research, 2014)
There is a discrepancy between publically available data from the United Network for Organ Sharing (UNOS) database and perception of the incidence of mortally burn-injured patients serving as organ donors. In the last 5 y, a single burn center referred several patients who went on to successfully donate multiple organs. However, UNOS data indicate very few referrals of patients with burn injuries nationwide. This discrepancy in UNOS-reported occurrences versus institutional experience prompted this work. UNOS data from 1988–2012 was examined for causes of death related to thermal injury, electrical injury, inhalation injury, or carbon monoxide poisoning. The National Burn Repository was examined for burn center death rates and patient characteristics of those with reported nonsurvivable burn injuries. Finally, a national survey queried the clinical experiences and educated opinions of burn center directors, transplant surgeons, and organ procurement organization (OPO) representatives regarding organ donation in the burn-injured population. Between 42% and 52% of those surveyed responded. Survey data indicate that at least 61 patients with burn-related injuries have served as organ donors in the past 5 y alone, versus 23 identified in 24 y of UNOS data. Survey data also indicate that inhalation injuries were the most common burn-related injuries seen before successful organ procurement. Kidneys were the most commonly donated organs, but all major organs and tissues were represented in the experiences of surgeon and organ procurement organization respondents. Up to 10% surgeon respondents believe that patients with burn injuries should not be referred for possible organ donation. There are more organs donated by patients with mortal burn injuries than currently available UNOS data would suggest. Survey data suggest that these patients should be able to contribute successfully to the supply of organs needed by those on transplant waiting lists, but remain inconsistently recognized as such a resource. Knowledge about long-term organ and tissue viability from burn-injured patients is lacking, and should be the focus of future research.